Sagiyah Salikin tahu menjaga tuah - Ruhayah Mahmod (Pelanduk Publications (M) Sdn. Bhd., 2017)
On biography of Sagiyah Salikin, a wife of Tun Ahmad Sarji bin Abdul Hamid, Chief Secretary to the Government of Malaysia, serving from February 1, 1990 to September 16, 1996